Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Cu-Catalyzed iminative hydroolefination of unactivated alkynes en route to 4-imino-tetrahydropyridines and 4-aminopyridines - Kumar, Ravi; Thorat, Shridhar H.; Reddy, Maddi Sridhar (Chemical Communications, 2016)
A general method for synthesizing 4-imino tetrahydropyridine derivatives is achieved, from readily available beta-enaminones and sulfonyl azides, which comprises a sequential copper catalyzed ketenimine formation and its hitherto inaccessible intramolecular hydrovinylation. The products are shown as ready precursors for highly valuable 4-sulfonamidopyridine derivatives via DDQ mediated oxidation.

Synthesis and characterization of simple cost-effective trans-A(2)BC porphyrins with various donor groups for dye-sensitized solar cells - Kumar, Ravi; Sankar, Muniappan; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (New Journal of Chemistry, 2016)
We have designed and synthesized a series of simple cost-effective 'push-pull' Zn(II) porphyrin dyes containing various electron donors such as 2-thienyl, pyrenyl, phenyl, 4'-bromophenyl, 4'-tbutylphenyl and 4'-carboxyphenyl acceptor moieties in three steps. Their optical absorption spectra, electrochemical redox and photovoltaic properties have been investigated in detail. The overall power conversion efficiencies (Z) of DSSCs based on these dyes are in the range of 2.1 to 4.2% and highly depend on their donor moiety. The incorporation of trans-10,20-dimesityl groups is highly beneficial for preventing the p-p aggregation among the porphyrin moieties, thus favorably suppressing the charge recombination and intermolecular interaction. Among all, pyrenyl appended Zn(II) porphyrin has exhibited a higher power conversion efficiency of 4.2% under 1 sun illumination due to the extended p-conjugation and electron donating ability of the pyrenyl moiety.

Decay processes in cationic alkali metals in microsolvated clusters: a complex absorbing potential based equation-of-motion coupled cluster investigation - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Theory and Computation, 2022)
We have employed the highly accurate complex absorbing potential based ionization potential equation-of-motion coupled cluster singles and doubles (CAP-IP-EOM-CCSD) method to study the various intermolecular decay processes in ionized metals (Li+, Na+, K+) microsolvated by water molecules. For the Li atom, the electron is ionized from the 1s subshell. However, for Na and K atoms, the electron is ionized from 2s and both 2s and 2p subshells, respectively. We have investigated decay processes for the Li+-(H2O)(n) (n = 1-3) systems, as well as Na+-(H2O)(n) (n = 1, 2), and K+-H2O. The lithium cation in water can decay only via electron transfer mediated decay (ETMD) as there are no valence electrons in lithium. We have investigated how the various decay processes change in the presence of different alkali metal atoms and how the increasing number of water molecules play a significant role in the decay of microsolvated systems. To see the effect of the environment, we have studied Li+-NH3 in comparison to Li+-H2O. In the case of Na+-H2O, we have studied the impact of bond distance on the decay width. The effect of polarization on decay width was checked for the X+-H2O (X = Li, Na) systems. We used the PCM model to study the polarization effect. We have compared our results with existing theoretical and experimental results wherever available in the literature.

Mapping the finite-temperature behavior of conformations to their potential energy barriers: case studies on Si6B and Si5B clusters - Maneri, Asma H.; Singh, Chandrodai Pratap; Kumar, Ravi; Maibam, Ashakiran; Krishnamurty, Sailaja (ACS Omega, 2022)
Dynamical simulations of molecules and materials have been the route to understand the rearrangement of atoms within them at different temperatures. Born-Oppenheimer molecular dynamical simulations have further helped to comprehend the reaction dynamics at various finite temperatures. We take a case study of Si6B and Si5B clusters and demonstrate that their finite-temperature behavior is rather mapped to the potential energy surface. The study further brings forth the fact that an accurate description of the dynamics is rather coupled with the accuracy of the method in defining the potential energy surface. A more precise potential energy surface generated through the coupled cluster method is finally used to identify the most accurate description of the potential energy surface and the interconnected finite-temperature behavior.

Well-defined hierarchical teddy bear sunflower-like NiCo2O4 electrocatalyst for superior water oxidation - Bodhankar, Pradnya M. M.; Dhawale, Dattatray S. S.; Giddey, Sarbjit; Kumar, Ravi; Sarawade, Pradip B. B. (Sustainable Energy & Fuels, 2022)
The development of a robust and efficient electrocatalyst for water oxidation is challenging due to the large overpotential requirement to transfer four electrons. Herein, a novel spinel-type hierarchical teddy bear sunflower-like NiCo2O4 electrocatalyst was synthesized through the facile solvothermal process and evaluated for the challenging and demanding oxygen evolution reaction (OER) in the water electrolysis process. The teddy bear sunflower-like NiCo2O4 supported on nickel foam (NF) delivers a current density of 50 mA cm(-2) at a small water oxidation overpotential (eta(50) = 319 mV) which is significantly lower than that of the corresponding spherical NiO/NF (eta(50) = 338 mV), and sea-urchin like Co3O4/NF (eta(50) = 357 mV). A large specific and electroactive surface area, as well as a high TOF value exhibited by the hierarchical teddy bear sunflower-like NiCo2O4 electrocatalyst, demonstrates the potential of NiCo2O4 to catalyze the water oxidation reaction efficiently. The impact of the near-Fermi-level d-orbital states in NiCo2O4 electrocatalyst for boosting OER activity was unveiled by the density functional theory calculation. The stable performance even after 16 h and high catalyst utilization of the hierarchical teddy bear sunflower-like NiCo2O4 through the OER indicates that the catalyst is highly suitable for the large-scale water oxidation process.

Effect of charge and solvation shell on non-radiative decay processes in s-block cationic metal ion water clusters - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2023)
Intermolecular Coulombic decay or electron transfer-mediated decay are the autoionization processes through which a molecule can relax. This relaxation is only possible if the inner valence's ionization potential (IP) exceeds the system's double ionization potential (DIP). To study the effects of charge and solvation shell, we have calculated the IP, DIP values, and lifetime of Na-2s and Mg-2s temporary bound states in various optimized structures of Na+-(H2O)(n) and Mg2+-(H2O)(n) (n = 1-5) micro-solvated clusters, where n water molecules are distributed in a way that some are directly bound to the metal ion and the rest to the water molecules. The first and second solvation shells are the names for the former and the latter water-binding positions, respectively. For a given n, the lifetime of decaying states is longer when water molecules are in the second solvation shell. We found that the Mg-2p state can decay for all n values in Mg2+-(H2O)(n) clusters, whereas the Na-2p state's decay is possible for n >= 2 in Na+-(H2O)(n) clusters. Our findings highlight the influence of metal ions' charge, different solvation shell structures, and the number of water molecules on the decay rate. These systems are relevant to the human body, which makes this study significant.

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon

Insights into adsorption of various gases on extra-framework cations of zeolite: a dispersion corrected DFT study on zeolite cluster models with Li plus , Na plus and K plus ions - Devasia, George; Kumar, Ravi; Vaval, Nayana; Krishnamurty, Sailaja (Microporous and Mesoporous Materials, 2023)
Design of an economical and sustainable gas separation material is relevant in several industrial processes. Zeolites with tunable pore sizes are ideal molecular sieves of many gases. The adsorption centers of these molecular sieves are extra-framework Lewis acid centers. In this study, we attempt to delineate the electronic properties of such centers (Li+, Na+ and K+) and their sorption properties towards N2, O2, CO, CO2 and H2. Negative framework of zeolites are modeled using different cluster models that present distinct electronic environment and role of this environment on the Lewis acidity of the cation. The sorption property towards different gases is evaluated using dispersion corrected DFT studies. The results obtained are benchmarked for one of the studied model using CCSD calculations. The results indicate that while the local environment modulates the adsorption properties, the relative adsorption properties between different ions follow the same order irrespective of the type of negative framework modeled. This reveals that intrinsic atomic properties of the charge compensating cations drive the sorption properties of the zeolites. Adsorption energies compounded with the analysis of IR stretching frequencies of the adsorbed gases reveals that Li centers shows molecular adsorption (charge donation to the cationic centers) towards N2 as compared to O2 and towards CO2/CO as compared to H2, demonstrating the applicability of Li-Zeolites as ideal membranes for oxygen concentrators and syngas separation. These adsorption studies are ratified by the BOMD simulations at 300 K, where H2 and O2 desorbs while N2, CO and CO2 remains adsorbed to the cationic site.
Keywords: BOMD simulation; CO/CO2/H2 separation; Extra-framework cation; N2/O2 separation; zeolites

Relaxation of the 2a1 ionized water dimer: an interplay of intermolecular Coulombic decay (ICD) and proton transfer processes - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2024)
This article investigates the relaxation dynamics of the ionized 2a(1) state of a water molecule within a water dimer. The study was motivated by findings from two previous pieces of research that focused on the relaxation behaviors of the inner-valence ionized water dimer. The present study discloses an observation indicating that water dimers display specific fragmentation patterns following inner-valence ionization, depending on the position of the vacancy. Vacancies were created in the 2a(1) state of the proton-donating water molecule (PDWM) and proton-accepting water molecule (PAWM). Utilizing Born-Oppenheimer molecular dynamics simulations, the propagation of the 2a(1) ionized state was carried out for both scenarios. The results revealed proton transfer occurred when the vacancy resided in the PDWM, accompanied by the closing of decay channels for O-H bond distance (RO-H) > 1.187 & Aring; (matching Richter et al.'s findings). Conversely, when vacancy was on PAWM, we observed no closing of decay channels (aligning with Jahnke et al.'s findings). This difference translates to distinct fragmentation pathways. In PDWM cases, 2a(1) state ionization leads to H3O+ -OH center dot formation. In contrast, PAWM vacancies result in decay pathways leading to H2O+-H(2)O(+ )products.

Synthesized novel chromogenic reagent and sensor: detection and identification of dichlorvos - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Mandlik, Prashant R.; Jadhao, Nitin L.; Gajbhiye, Jayant M.; Kumar, Ravi; Vaval, Nayana (Heliyon, 2024)
We developed a novel chromogenic reagent and sensor by selective approach, for the detection and identification of dichlorvos, which we tested with the thin layer chromatography method. For the first time, we reported in situ-generated glyoxal as a hydrolysis product, which then interacts with isoniazid to produce a yellow-colored cyclic compound. We used well-known spectroscopic techniques to confirm the chemical identity of the final product. We initially investigated the reaction using a variety of approaches, followed by attempts to establish the reaction mechanism using Density Functional Theory by Gaussian software.
Keywords: DFT analysis; Dichlorvos; Gloyxal; Hydrazone; Isoniazid

Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Accessing electron-deficient π-extended pyrenes via non-K-region fusion - Dongre, Sangram D.; Kumar, Viksit; Kumar, Ravi; Babu, Sukumaran Santhosh (ORGANIC LETTERS, 2025)
This study presents a new class of pyrene derivatives featuring non-K-region fusion and electron-deficient pi-extension. By strategically introducing electron-withdrawing groups at the non-K positions, the optical and redox properties of these compounds were significantly altered. For the first time, we report a non-K-region fused acceptor pyrene with an extended pi-skeleton. The detailed characterizations revealed pronounced shifts in both absorption and emission spectra, accompanied by a significant lowering of the LUMO energy levels. Our results highlight non-K region-fused pyrenes as a promising building block for next-generation organic semiconductors with tunable electronic properties.

Charge transfer effect on relaxation mechanism in hydrated pyrrole-water systems following N-2s ionization - Kumar, Ravi; Bhattacharjee, Kankana; Ghosh, Aryya; Vaval, Nayana (ChemPhysChem, 2025)
This study investigates the relaxation mechanisms of pyrrole and pyrrole-water clusters (C4H5N-(H2O)n, where n=0-3 \${n = 0 - 3}\$ ) following N-2s ionization of pyrrole. Using various theoretical methods, we focus on the influence of water molecules and charge transfer on these non-radiative relaxation pathways. Our simulations included pyrrole solvated in 494 explicit water molecules equilibrated at 300 K and also employed a polarizable continuum model (PCM) to make the system more realistic and gain additional insights. In hydrated environments, the hydrogen bonding network between pyrrole and surrounding water molecules facilitates enhanced non-radiative relaxation pathways following inner valence ionization. Since these are hydrogen bonding systems, we have explored the possibility of proton transfer, which could occur in conjunction with other electronic decay processes.
Keywords: ab initio-calculations; auger decay; charge transfer; proton transfer; pyrrole

Insights into the Chemical Durability and Structure of ZnO-Incorporated Sodium Borosilicate Glasses from Solid-State NMR - Illath, Kavya; Ananthanarayanan, Arvind; Banerjee, D.; Mishra, R. K.; Kumar, Ravi; Bhattacharya, D.; Kumar, Sanjay; Manohar, S.; Ajithkumar, T. G. (Journal of Physical Chemistry B, 2025)
ZnO-incorporated NBS glasses have been studied for their application as a matrix for nuclear waste immobilization. However, structural factors affecting chemical durability have not been established. In this study, the structural changes in NBSZn glasses across various Na2O/(B2O3 + ZnO) ratios are explored using multinuclear MAS, MQMAS NMR, and EXAFS techniques. The Na MAS and MQMAS studies reveal remarkable changes in the Na environment after ZnO incorporation, which leads to an increase in chemical durability. Based on the results from NMR and EXAFS, we rationalized the structure of this glass in terms of the modified random network (MRN) model. The glass network comprises a highly polymerized region and alkali percolation channels bordered by nonbridging oxygens from the depolymerized regions. The constriction of these percolation channels increases the chemical durability of the glass. Our findings will help in the advancement of Zn-containing NBS glasses as a promising matrix for nuclear waste immobilization.

Kekule diradicaloid with a naphthalene spacer - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2026)
The availability of a diverse array of carbenes led to the generation of a catalog of carbene based Kekule diradicaloids, but the linker in such molecules is mostly limited to phenylene or biphenylene. Here we have prepared a closed-shell Kekule diradicaloid (2) separated by a naphthalene moiety and stabilized by two capping 5-SIDipp [5-SIDipp = 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] from the reduction of the corresponding dication (1). The combined experimental and computational studies confirm that 2 is in a closed-shell singlet state exhibiting a singlet-triplet energy difference (Delta ES-T) of 18.7 kcal/mol, which is considerably lower than Thiele's version (29.1 kcal/mol).

Solvent and pH effects on the ionization energies of bio-organic molecules: a case study of alanine and glycine - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Physical Chemistry Chemical Physics, 2026)
The ionization energies (IEs) and double ionization energies (DIEs) of the amino acids alanine and glycine have been studied in the gas phase and a polarizable continuum model (PCM) to account for solvent effects. Amino acids undergo structural modifications, particularly in their functional groups, in response to changes in their chemical environment, such as pH. Four possible different structural forms, neutral (NH2-R-COOH), zwitterionic (NH3+-R-COO-), deprotonated (NH2-R-COO-), and protonated (NH3+-R-COOH), were generated for each amino acid. In this study, we use these four forms to explore the effects of protonation and deprotonation (pH effect) on the IEs of inner-valence states. In amino acids, IEs and DIEs are essential for evaluating the energetic viability of inner-valence-initiated non-radiative decay processes, such as interatomic Coulombic decay (ICD). All IE and DIE values were calculated using the complete active space perturbation theory (CASPT2) method. A comparison is made across gas-phase and PCM environments to assess the impact of solvation. The observed variations in IE and DIE values indicate a lot about alanine and glycine's electronic structure and chemical reactivity under different physiological and environmental conditions (pH effect and solvation), hence improving our understanding of their functional roles in biochemical systems.